STRATEGI GURU DALAM PEMBELAJARAN PAI PADA ANAK BERKEBUTUHAN KHUSUS - Wela Oktari; Hendra Harmi; Deri Wanto (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2020)
Every human being cannot choose whether he/she will be born normally or not. To be born normally or not is of Allah's decision. Every parent must realize this so that they will not regard their children born as individuals with special needs as disgrace and disaster. Such children deserve education and teaching because they are also given the potential by Allah to understand their needs to survive. How to educate them becomes an interesting issue to be studied. Thus, this study qualitatively addressed teachers’ strategies in Islamic education learning for children with special needs in SLBN 1 Kepahiang, Bengkulu. The findings of this study exhibited that the teachers’ strategies in Islamic Education learning for children with special needs in SLBN 1 Kepahiang were initiated by taking account of several aspects, namely: 1) service to students focused on the patterns of teachers’ behavior in educational interactions at school; 2) curriculum adjustment; and 3) the implementation of learning by applying the methods of demonstration and habituation, especially for the materials of worshiping practices.Keywords: Strategies, Islamic Education Learning, Children with Special Needs